A Simple Approach to Regulate a PVTOL System Using Matching Conditions - Aguilar-Ibanez, Carlos; Suarez-Castanon, Miguel S.; Meda-Campaña, Jesus; Gutierrez-Frias, Octavio; Merlo-Zapata, Carlos; Martinez-Castro, Jesus A. (Journal of intelligent & robotic systems, 2020)
In this work, based on shaping an energy function, it is introduced an output-feedback regulation control law for a Planar Vertical Takeoff and Landing (PVTOL) aircraft. To this end, a version of the matching control energy method is used to construct the Lyapunov candidate function and the stabilizer controller to regulate the PVTOL aircraft. The non-measurable system velocities are recovered using a suitable exact differentiator observer, achieved through super-twisting based observer. The theorem of LaSalle, together with some tools from the cascade system theory, was used to carry out the closed-loop stability analysis. Using a suitable finite time-varying identificator, the obtained controllers were improved to compensate bounded, smooth, and matching perturbations. Numerical simulations were included to test the effectiveness of the obtained controller.